From Farm to Fork: An Architectural Response to Food Insecurity & Bridging the Natural World, Food Producers, & Consumers for a Community Resilient Food Landscape - Gray, Bonnie (Auckland University of Technology, 2026)
With the decline of our environment’s health and the failings of Aotearoa’s food system, this project identifies the dangers of food insecurity and the fragmentation between food producers, consumers, and the natural environment. Urban sprawl into food-productive landscapes threatens domestic food security, diminishing versatile soils, and creating tension between new residents and existing farmers. This research is an architectural solution that mediates these tensions by designing a built food haven in Pukekohe, Aotearoa. The architecture connects food producers, consumers, and the environment within a food hub that provides community infrastructure, knowledge exchange, accessibility to local food production, food sovereignty, and collaborative initiatives between the three stakeholders. Bridging these relationships in place fosters awareness of food system and living system processes that food production and people’s health depend on.